Tinjauan Pelaksanaan Review Rekam Medis dalam Rangka Persiapan Akreditasi Rumah Sakit Berdasarkan Standar Akreditasi SNARS-1 di RSUD Sultan Thaha Saifuddin Kabupaten Tebo Provinsi Jambi - Novi Mulyani Putri; Witri Zuama Qomarania; Hosizah Hosizah (Indonesian of Health Information Management Journal (INOHIM), 2021)
AbstractSultan Thaha Saifuddin Hospital is heading towards the implementation of SNARS-1. The first phase of accreditation in 2016 uses the 2012 version with only four services (SKP, HPK, KPS, PPI) so that there is no medical record review assessment as in the MIRM 13.4 SNARS-1 assessment element. Currently, Sultan Thaha Saifuddin Hospital must adjust the medical record review with the MIRM standard on SNARS-1. Field Study Practices at the Sultan Thaha Saifuddin Hospital, Tebo Jambi Regency on April 1, 2019 to April 20, 2019 with the aim of knowing the implementation of medical record reviews based on the SNARS-1 accreditation standard. Methods of data collection are carried out by observation and interviews using observation sheets and interview guides. The results of the field study practice are: there is a team responsible for reviewing medical records called the medical record committee; there is an SPO regarding medical record review; review of medical records using an open, closed, and recapitulation review form; There was an increase in the quality of medical records based on the results of reviews between period 1 and period 2, namely from 89.65% to 96.8% on timeliness, an increase from 95.4% to 97.6% in legibility, and an increase from 97, 6% to 99.2% on completeness of medical records. The implementation of reviewing medical records at Sultan Thaha Saifuddin Hospital is in accordance with the applicable SPO. The implementation of the review is also in accordance with the SNARS-1 assessment elements.Keyword: medical record, completness, Accreditation Assessment SNARS-1                                                                AbstrakRSUD Sultan Thaha Saifuddin sedang menuju implementasi SNARS-1. Akreditasi tahap pertama tahun 2016 menggunakan versi 2012 baru sebatas empat pelayanan (SKP, HPK, KPS, PPI) sehingga belum ada penilaian review rekam medis seperti pada elemen penilaian MIRM 13.4 SNARS-1. Saat ini, RSUD Sultan Thaha Saifuddin harus menyesuaikan review rekam medis dengan standar MIRM pada SNARS-1. Praktik Belajar Lapangan dilakukan di RSUD Sultan Thaha Saifuddin Kabupaten Tebo Jambi pada tanggal 01 April 2019 sampai 20 April 2019 dengan tujuan untuk mengetahui pelaksanaan review rekam medis berdasarkan standar akreditasi SNARS-1. Metode pengumpulan data dilakukan dengan observasi dan wawancara menggunakan lembar observasi dan panduan wawancara. Hasil praktik belajar lapangan yaitu: terdapat tim yang bertanggung jawab pada review rekam medis disebut panitia rekam medis; terdapat SPO tentang review rekam medis; review rekam medis menggunakan form review terbuka, tertutup, serta rekapitulasi; terdapat kenaikan kualitas rekam medis berdasarkan hasil review antara periode 1 dan periode 2 yaitu dari 89,65% menjadi 96,8% pada ketepatan waktu, terjadi kenaikan  dari 95,4% menjadi 97,6% pada keterbacaan, serta terjadi kenaikan dari 97,6% menjadi 99,2% pada kelengkapan rekam medis. Pelaksanaan review rekam medis di RSUD Sultan Thaha Saifuddin telah sesuai dengan SPO yang berlaku. Pelaksanaan review juga telah sesuai dengan elemen penilaian SNARS-1.Kata Kunci: rekam medis, kelengkapan, akreditasi SNARS-1